2012
DOI: 10.2166/wst.2012.949
|View full text |Cite
|
Sign up to set email alerts
|

WEF/WERF study of BNR plants achieving very low N and P limits: evaluation of technology performance and process reliability

Abstract: The Water Environment Research Foundation (WERF) funded a two-year comprehensive study of nutrient removal plants designed and operated to meet very low effluent total nitrogen (TN) and total phosphorus (TP) concentrations. WERF worked with the Water Environment Federation (WEF) to solicit participation of volunteers and provide a forum for information exchange at workshops at its annual conferences. Both existing and new technologies are being adapted to meet requirements that are as low as 3.0 mg/L TN and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…However, in the first phase of the program the association found that it could achieve nutrient discharge reduction more cheaply through operational and minor capital improvements; the required reduction was not severe enough to stimulate demand for credits. When regulatory requirements for trading are weak and firms are able to apply on‐site technologies (Bott et al ., ), demand for credits is low.…”
Section: The Economic and Institutional Environmentmentioning
confidence: 99%
“…However, in the first phase of the program the association found that it could achieve nutrient discharge reduction more cheaply through operational and minor capital improvements; the required reduction was not severe enough to stimulate demand for credits. When regulatory requirements for trading are weak and firms are able to apply on‐site technologies (Bott et al ., ), demand for credits is low.…”
Section: The Economic and Institutional Environmentmentioning
confidence: 99%
“…The technologies for biological wastewater treatment has evolved from conventional biological nutrient removal, through enhanced biological nutrient removal to the limit of present technology [1][2][3][4]. For sensitive water bodies, discharging of wastewater with total nitrogen (TN) concentration of 3 mg/L and total phosphorus (TP) of 0.1 mg/L or even lower has been set as discharging standard [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For sensitive water bodies, discharging of wastewater with total nitrogen (TN) concentration of 3 mg/L and total phosphorus (TP) of 0.1 mg/L or even lower has been set as discharging standard [2][3][4]. The biological removal of nitrogen (N) is mainly achieved by combining nitrification and denitrification conventional processes.…”
Section: Introductionmentioning
confidence: 99%
“…The TN removal efficiencies of the four WWTPs and their summary statistics (50th, 95th, and 99th percentiles) for daily performance based on historical plant data over a three-year period were published by Bott et al (2012). The 95th percentile is considered to capture the ''reliable" achievable performance for a WWTP (Bott et al, 2012).…”
Section: Leachate and Wastewater Co-treatment Simulationsmentioning
confidence: 99%
“…The 95th percentile is considered to capture the ''reliable" achievable performance for a WWTP (Bott et al, 2012). The 50th percentile values represent the median as opposed to the average.…”
Section: Leachate and Wastewater Co-treatment Simulationsmentioning
confidence: 99%